Pelatihan penyusunan laporan keuangan berdasarkan SAK ETAP dengan komputer pada koperasi Serba Usaha Mandiri, Desa Manisrenggo, Klaten - Wiwin Windihastuty; Sri Rahayu; Krisna Adiyarta; Swasti Broto (Unri Conference Series: Community Engagement, 2020)
Koperasi Usaha Mandiri in Manisrenggo, Klaten, Java has carried out intermediation activities by collecting funds from all cooperative members in form of savings to be distributed again to members who need funds in the form of loans. Koperasi has significant public accountability, but because it has not registered as a public company, Koperasi Usaha Mandiri is only responsible for the funds of its members. The purpose of this Community Service activity is to improve the management's ability to prepare financial reports based on SAK ETAP either manually or using a computer system. This activity begins with an introduction and submission of material on financial reports or financial reports based on SAK ETAP and is followed by training on recording using Excel. The material prepared in this training includes the process of preparing financial reports, namely making journals, ledgers, balance reports, reports on business results and cash flow reports. After attending the training, the management of the Koperasi has increased their understanding of the importance of implementing SAK ETAP to present cooperative financial reports. Increased understanding of cooperative management regarding the concepts and basic principles of cooperative accounting, elements of recognition, measurement and presentation of financial statements in accordance with SAK ETAP, can assist them in the process of preparing and presenting financial statements in future periods.